2020
DOI: 10.3390/ijms21051582
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Factors and EV-miRNAs Orchestrate the Healing Capacity of Adipose Mesenchymal Stem Cells for the Treatment of Knee Osteoarthritis

Abstract: Mesenchymal stem cells (MSCs) derived from adipose tissue and used either as expanded cells or minimally manipulated cell preparations showed positive clinical outcomes in regenerative medicine approaches based on tissue restoration and inflammation control, like in osteoarthritis (OA). Recently, MSCs’ healing capacity has been ascribed to the large array of soluble factors, including soluble cytokines/chemokines and miRNAs conveyed within extracellular vesicles (EVs). Therefore, in this study, 200 secreted cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 110 publications
(112 reference statements)
5
53
0
Order By: Relevance
“…Under this final analysis, miR-101-3p emerged as the best candidate (geomean of 1.32), tightly followed by miR-22-5p (1.41). Conversely, miR-423-5p (8) and U6 snRNA (9) clearly ranked last, making their choice unfavorable.…”
Section: Rgs Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Under this final analysis, miR-101-3p emerged as the best candidate (geomean of 1.32), tightly followed by miR-22-5p (1.41). Conversely, miR-423-5p (8) and U6 snRNA (9) clearly ranked last, making their choice unfavorable.…”
Section: Rgs Stability Analysismentioning
confidence: 99%
“…As an example, in the orthopedic field, which is one of the most actively studied areas in regenerative medicine, miRNA-enriched MSC-EVs were shown to promote cartilage regeneration [5,6] by modulating ECM production. Similarly, in adipose-derived MSCs (ASCs), inflammatory priming of cells was able to modulate the EVs incorporation of miRNAs involved in both cartilage homeostasis and macrophage M2-polarization [8,9]. Thus, there is a growing interest in both the discovery and characterization of new MSC-EVs for their future use as natural or engineered delivery platforms in regenerative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, miR-24-3p upregulation could promote intervertebral disc degeneration through IGFBP5 and the ERK signaling pathway [25]. According to the report by Ragni et al [17] who showed a strong capacity for adipose-derived MSCs (ASCs) to reduce matrix degradation activities, we thus inferred that miR-24-3p suppressed OA progression might via inhibiting apoptosis, in ammation and ECM degradation.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Shen et al [16] demonstrated that miR-24-3p may ameliorate in ammatory response and cellular apoptosis in hepatic I/R process, which might be a potential therapeutic target for preventing liver I/R development and progression. Interestingly, a recent study by Ragni et al [17] who pointed that miR-24-3p was involved in adipose-derived mesenchymal stem cells (ASCs) regulating cell homeostasis and regenerative pathways in an OA-resembling environment. However, the involvement and underlying mechanism of miR-24-3p in chondrocyte injury associated with the pathogenesis of OA remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al demonstrated that ADSCs suppress osteoclastogenesis and bone erosion in collagen-induced arthritis [63]. In addition, secreted factors and EV-miRNAs orchestrate the healing capacity of ADSCs in treating knee osteoarthritis [64]. Cowan et al demonstrated that the effects of ADSC transplantation repairing skull defect was great, and there were no needs for any treatment for ADSCs in vitro or adding any simulating factors.…”
Section: Adsc Transplantation In Bone Joint and Muscle Systemmentioning
confidence: 99%